2010
DOI: 10.1021/ol1014174
|View full text |Cite
|
Sign up to set email alerts
|

Enyne [4 + 4] Photocycloaddition: Bridged 1,2,5-Cyclooctatrienes

Abstract: Enyne photocycloaddition with a 2-pyridone yields a mixture of products including amide-bridged 1,2,5-cyclooctatrienes, the first examples of enyne [4 + 4] adducts. Four regio- and stereochemical isomers of the [4 + 4] adduct are possible. All appear to be too strained to be isolated, but they have been identified as their [2 + 2] cyclobutane dimers. Cyclobutane and cyclobutene adducts have also been isolated, [2 + 2] addition products possibly related to the unstable [4 + 4] adducts via Cope rearrangement. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…[1,2] Both inter-a nd intramolecular examples have been reported as well as catalysis by acids and transition metals,a ll of which have been extensively investigated. [3,4] Thecycloadducts formed in these higher-order cycloadditions are incapable of isomerizing to arenes however, and unless an alternative pathway to relieve strain is available,t he products often undergo dimerization reactions that result in complex mixtures. 1!3,S cheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Both inter-a nd intramolecular examples have been reported as well as catalysis by acids and transition metals,a ll of which have been extensively investigated. [3,4] Thecycloadducts formed in these higher-order cycloadditions are incapable of isomerizing to arenes however, and unless an alternative pathway to relieve strain is available,t he products often undergo dimerization reactions that result in complex mixtures. 1!3,S cheme 1).…”
mentioning
confidence: 99%
“…Recently we reported that 1,3-enynes can be participants in [4+ +4] cycloadditions and found them to work well with pyridones (4, 7), pyrones and anthracene. [3,4] Thecycloadducts formed in these higher-order cycloadditions are incapable of isomerizing to arenes however, and unless an alternative pathway to relieve strain is available,t he products often undergo dimerization reactions that result in complex mixtures. [5,6] Stability through steric shielding can be designed into strained allenes,asdescribed by Johnson and Price.…”
mentioning
confidence: 99%
“…2 During our investigations of 2-pyridone photochemistry we have studied its cycloaddition with 1,3-enynes and discovered two different pathways based on the presentation of the enyne. 3,4 When the enyne is attached through the alkyne (1), only [4+4] cyclization results and the highly strained allene product 2 is, in most cases, unstable and undergoes further reaction. In contrast, when the enyne is linked to the pyridone through the alkene (3), only [2+2] products are observed (see Scheme 1).…”
mentioning
confidence: 99%
“…25 Cope rearrangement of the 1,2,5-heptatriene unit found in 27 to give a 1,5-enyne (e.g., 24) had been considered in our earlier enyne-pyridone photochemistry studies but was believed to be an unlikely pathway. 11 Huntsman demonstrated that the parent 1-hexen-5-yne underwent Cope rearrangement to give 1,2,5-hexatriene at 340°C. 26 Computational studies suggest that these pathways do not require radical intermediates.…”
mentioning
confidence: 99%